Antimycobacterial activity evaluation and MIC determination of liophilizated hydroalcoholic extracts of Bixa orellana L., Bixaceae - Silva,Renata B. (2010)
Bixa orellana is used in popular medicine against several diseases. Extracts of its fruit, root and leaf presented antimicrobial activity, while seed extract showed negative results. This study aimed at verifying the antimycobacterial activity of B. orellanalyophilized hydroalcoholic extracts over Mycobacterium tuberculosis, and determine the Minimum Inhibitory Concentration against five bacteria. Antimycobacterial activity was determined by diffusion technique, while MIC was assessed by diffusion and colorimetric analysis. MICs were 0.3, 0.5 and 0.2 mg/mL respectively, for leaf, root and stem extracts, against M. tuberculosis. Stem's extract showed 1.2 mg/mL for B. cereus, 1.53 mg/mL for S. aureusand S. typhimurium, 4.50 mg/mL for P. aeruginosaand 8.01 mg/mL for P. mirabillis.Leaf extracts showed 0.66 mg/mL for P. aeruginosa, 0.94 mg/mL for P. mirabillis, 1.88 mg/mL for S. aureus, 3.95 mg/mL for B. cereusand 8.37 mg/mL for S. typhimurium. Root's extracts showed 0.25 mg/mL for P. aeruginosa,0.31 mg/mL for S. aureus, 0.62 mg/mL for S. typhimuriumand 3.00 mg/mL for B. cereusand P. mirabillis. Leaf and stem extracts showed antimycobacterial activity. MICs were lower in colorimetric analysis than in agar diffusion. Extracts revealed bacteriostatic activity against the five bacterial.